Three new species of Telmatoscopus Eaton, 1904 (Diptera, Psychodidae) from Brazil - Bravo, Freddy; Souza, Isys; Santos, Claudiney Biral Dos; Ferreira, Adelson Luiz (Zootaxa, 2011)
Three new species of Telmatoscopus auct. (nec Eaton, 1904) from Brazil are described, one from Paraná State, southern Brazil, and two from Espírito Santo State, southeastern Brazil. Ten species of Telmatoscopus s. l. are currently known from the Neotropical region, including the three new species described here. An identification key for males of all Neotropical species of Telmatoscopus s. l. is presented.